Effect of temperature on the yield of lignin extracted using microwave-sssisted acetosolv from empty fruit bunch fibers - Muhammad Nor Arifin, Yaakob; Rasidi, Roslan; Nurjannah, Salim; Siti Noor Hidayah, Mustapha; Sarani, Zakaria; Chia, Chin Hua; Mohd Shaiful, Sajab; Nai Yuh, Peter Yek (Trans Tech Publications Ltd, Switzerland, 2020)
Acetosolv technique is considered as one of the best alternative ways to extract technical lignin from biomass as it has high efficiency and environmentally friendly. In this study, microwave assisted acetosolv technique was used to extract lignin from oil palm empty fruit bunch (OPEFB) in the presence of 3% sulfuric acid catalyst reacted at various temperature. The yield of the extracted acetosolv lignin was calculated using the modified Technical Association of the Pulp and Paper Industry biomass composition analysis (TAPPI) method. The result showed that, as the temperature increased from 90 to 110 °C, the yield of lignin extracted also increase from 43.07 to 76.98%. The presence of guaiacyl and p-coumarate indicates the presence of active sites at C-3 and C-5 of the aromatic ring for polymerization reactions. Scanning Electron Microscopy images showed that removal of lignin is intensified as the microwave-assisted acetosolv temperature increased.